IMPROVING STUDENT’S COMPREHENSION IN READING DESCRIPTIVE TEXT BY USING 3-2-1 STRATEGY - Yulharmaini,, Riya; ., Sofian; Wijaya, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research was carried out to improve the student’s comprehension in reading descriptive text by using 3-2-1 strategy. It was a Classroom Action Research which was conducted in three cycles. The subject of this research was grade XD, numbering 36 students. The data was collected using observation checklist and field notes. It also used mean score. The results indicated the student’s comprehension in reading descriptive text improve very well by applying 3-2-1 teaching strategy. The improvement to students’ reading comprehension was better in the third cycle than the first and second cycle which was shown by the percentage of student’s achievement. In the first cycle, the students achieved 55.55% ; in the second cycle, the students achieved 71.66%; while in the third cycle, the students achieved 75.27% Keywords : 3-2-1 Strategy, Descriptive Text, Comprehension in Reading Abstrak: penelitian ini dilaksanakan untuk meningkatkan pemahaman siswa dalam membaca teks deskriptif dengan menggunakan strategi 3-2-1. Penelitian ini adalah sebuah penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Subjek dari penelitian ini adalah kelas XD, yang berjumlah 36 siswa. Data penelitian dikumpulkan melalui ceklis observasi dan catatan lapangan. Analisa data juga dilakukan dengan cara mencari nilai rata-rata. Hasil penelitian ini menunjukkan pemahaman siswa dalam membaca teks deskriptif meningkat sangat baik. Dengan menerapkan strategi mengajar 3-2-1. Peningkatan pemahaman siswa lebih baik pada siklus ketiga daripada siklus pertama dan kedua. Sebagaimana yang ditunjukkan oleh hasil persentase dari hasil yang di capai siswa. Pada siklus pertama, persentase siswa adalah 55.55%; pada siklus kedua persentase siswa adalah 71.66%; sedangkan pada siklus ketiga, persentase siswa adalah sebesar 75.27% Kata kunci : Strategi 3-2-1, Teks Deskriptif, Pemahaman dalam membaca